2019
DOI: 10.1063/1.5099271
|View full text |Cite
|
Sign up to set email alerts
|

Syringe infusion pump with absolute piston displacement control

Abstract: A vast majority of syringe pumps operate on stepper motors, which limits their effectiveness for precision fluid delivery using estimation algorithms. Such a system also hampers the ability to ascertain if the infusion or aspiration instruction has been correctly carried out in the event of power interruptions. To address this issue, a linear servo based actuator system is described to provide absolute indications of the plunger position. System performance in terms of linearity and reliability of plunger tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A syringe pump large volume extruder with a 60 mL syringe and a 100 μm nozzle diameter was designed by Pusch et al 37 Several syringe pumps have been developed for the syringe-based 3D printing technology. [38][39][40] An opensource syringe pump with the ability to infuse the liquid and refill the empty syringe was recently developed by Samokhin et al 41 Sather et al demonstrated that a syringebased 3D printer is suitable for high viscosity resins. 42 Meanwhile Voet et al demonstrated that cracking resulting from shrinkage stress can be significantly reduced using high viscosity resins.…”
Section: Msde Papermentioning
confidence: 99%
“…A syringe pump large volume extruder with a 60 mL syringe and a 100 μm nozzle diameter was designed by Pusch et al 37 Several syringe pumps have been developed for the syringe-based 3D printing technology. [38][39][40] An opensource syringe pump with the ability to infuse the liquid and refill the empty syringe was recently developed by Samokhin et al 41 Sather et al demonstrated that a syringebased 3D printer is suitable for high viscosity resins. 42 Meanwhile Voet et al demonstrated that cracking resulting from shrinkage stress can be significantly reduced using high viscosity resins.…”
Section: Msde Papermentioning
confidence: 99%
“…The most promising drive in terms of functionality and possibility of automation of the process of farm animals vaccination is the electric drive of the plunger rod in devices for vaccination. The works of Ong J., Chung D., Lin E., Abid H., Liew O., Ng T., Jafarzadeh M., Farokhi F., Saidi I., El L., Ounip A. and Benrejeb M. recommend using the ultra-small stepper motor [4][5][6]. A prototype pump actuated by a piezoelectric stack actuator is developed and a PID feedback controller is designed for the drive of the injection device [7].…”
Section: Fig 3 Dosing Syringe "Hsw Henke-ject" (Germany)mentioning
confidence: 99%
“…An important feature of the syringe is that, apart from a hypodermic needle or nozzle, its hub may also be fitted with tubing to help direct the flow of a liquid some distance away. This has facilitated the development of infusion pumps that work by incorporating standard syringes with a mechanized actuator in order to deliver programmed volumes of liquid. , In this work, the use of plastic syringes to facilitate the safe handling of hydrochloric acid when it reacts with calcium carbonate to generate carbon dioxide gas is described. The utility of an inverted buret to capture the carbon dioxide gas generated and allow accurate volume determination with time is also demonstrated.…”
Section: Introductionmentioning
confidence: 99%